If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 8) + (-7x + -19) = 0 Reorder the terms: (8 + 6x) + (-7x + -19) = 0 Remove parenthesis around (8 + 6x) 8 + 6x + (-7x + -19) = 0 Reorder the terms: 8 + 6x + (-19 + -7x) = 0 Remove parenthesis around (-19 + -7x) 8 + 6x + -19 + -7x = 0 Reorder the terms: 8 + -19 + 6x + -7x = 0 Combine like terms: 8 + -19 = -11 -11 + 6x + -7x = 0 Combine like terms: 6x + -7x = -1x -11 + -1x = 0 Solving -11 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -1x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 0 + 11 -1x = 0 + 11 Combine like terms: 0 + 11 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 4x+5=87-2x | | 14xy-21yz= | | 4x+3y=30 | | 2y-7=y+9 | | (x+4)(x-1)=24 | | 2(x+5)-6=16 | | -15=x+(-16) | | X-Y+A=3 | | X-Y+Z=3 | | x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x | | 8y-2=7+6y | | (2x/3)=(4/7) | | 9x-1+8z-7x+z=0 | | 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 | | x+9=x-21 |